The photophysical properties of strongly coupled hybridized light-matter states in a classical physics perspective - Avramenko, Aleksandr (Physics and Chemistry of Solid State, 2025)
The Lorentz oscillator model is applied to a strongly coupled hybridized light-matter state. It is noted that the real part of the index undergoes rapid change in the area of the so-called “dark states.” This property of hybridized light-matter states could allow them to function as unorthodox optical materials in which their absorptive and refractive properties are selectively manipulated. In this manuscript, basic properties of hybrid light-matter states, also referred to as cavity polaritons, are reviewed. The Lorentz oscillator model is then applied to two types of light-matter states, one formed from coupling between a single exciton and a single cavity photon, and one formed from coupling two excitons to a single cavity photon. Furthermore, the simple harmonic oscillator model is used to estimate the spring constant of a diatomic molecule under strong light-matter coupling conditions. It is found that the spring constant is directly related to the photonic character of the system, with a higher photonic character resulting in a smaller spring constant.